(untitled) (Journal of Hama University, 2020)
Olive trees are the oldest fruit trees. This characteristic tree patient drought and can be cultivated in environments that are difficult to cultivate in other species. It is a long-standing tree that provides good income for farmers and provides employment opportunities for rural people .The objective of this research is to study the production costs and descriptive and standard economic analysis of the cost functions of the irrigated and unirrigated olive crops, and to identify the achieved volumes of economic efficiency and profit maximization. 331 samples were collected from (al Salamia) and its related villages for the agricultural season (2016 - 2017), the results of the study showed that the average cost of irrigated olive production (61435.25) sp / dunum, and the average profit achieved (25604.75) sp / dunum, the cost of 1 kg on average (226) sp / dunum and the average rate of profitability average (41.67) ). As for unirrigated Olive, it was the average of the total costs and the mean profit and the cost of 1 kg (42315.2, 18164.8) (223.9) sp / dunum, respectively, and the average rate of profitability (42.9%). Thus, the economic evaluation of Olive production in the study area indicates that it is profitable during the period studied it was also noted the rise costs of agricultural production necessary to carry out all the service operations needed by the crop, which is an obstacle to farmers to produce the desired quality of the crop, and using the economic standard models of the cost function by and determined the size of the economic efficiency, which amounted to (3645.24, 3120.7) kg of olives irrigated and unirrigated respectively the vast production was (3813.72 , 3510.37) kg for the irrigated and unirrigated olives, respectively, while the actual production reached (3454.4, 3078.81) kg for the irrigated and unirrigated olives is respectively, and by comparing these volumes with the average actual production of the studied area, the vast size of the profit, relatively less than the optimal size.